2011
DOI: 10.1590/s1679-62252011005000035
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and reproductive behavior of Sinaloa cichlid Cichlasoma beani (Jordan, 1889) in a tropical reservoir

Abstract: The population structure and reproductive condition of the Sinaloa cichlid Cichlasoma beani from samples obtained from June 2000 to July 2001 were determined. Samples in the first week each month from the largest trader of tilapia in the Aguamilpa Reservoir in Mexico and were caught in gillnets (9.6 and 11.4 cm stretch-mesh size). Of 596 specimens, there were 427 males and 169 females; monthly sex ratio, frequency of lengths by the multinomial distribution, timing of reproduction, condition index, and size at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…However, future studies are needed to verify this strategy in the species. The occurrence of reproduction in individuals cultured in the preliminary trial (weight 21 and 23 g and length 7.5 and 9.5 for female and male, respectively) differs from García‐Lizárraga et al (), who reported minimal reproductive size in the species as 10.5 cm (standard length). However, the findings of García‐Lizárraga et al () were obtained from in situ data.…”
Section: Discussioncontrasting
confidence: 69%
“…However, future studies are needed to verify this strategy in the species. The occurrence of reproduction in individuals cultured in the preliminary trial (weight 21 and 23 g and length 7.5 and 9.5 for female and male, respectively) differs from García‐Lizárraga et al (), who reported minimal reproductive size in the species as 10.5 cm (standard length). However, the findings of García‐Lizárraga et al () were obtained from in situ data.…”
Section: Discussioncontrasting
confidence: 69%
“…In this context, a study by [3] focused on the in situ reproductive population structure and its relation to the ecology of this species. Prior studies examined the effects of stocking density on growth and survival of this species under culture conditions [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…During the present study, C. beani was found in shallow waters of the San Pedro fluvial system at temperatures as high as 32°C. Apart (quotes) for San Pedro from an ecological study (García-Lizárraga et al, 2011) and a few parasite related studies (Caspeta-Mandujano et al, 1999, 2001Camacho et al, 2002;De Leon et al, 2008), there is no existing scientific information on the biology of C. beani. The development of culturing techniques has been a successful strategy to protect species.…”
mentioning
confidence: 99%